Workshop on Using Technology Applications as a Learning Media for MTs Al-Ittihad Pekanbaru Teachers: Workshop Penggunaan Aplikasi Teknologi Sebagai Media Pembelajaran Bagi Guru MTs Al-Ittihad Pekanbaru - Marwa*, Marwa; Herlinawati, Herlinawati; Awal, Raudhah; Safitri, Yona Dwi Tirta; Mutia, Jul Prima; Saputra, Novriandi Eka (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2024)
The workshop on using technology applications as a learning medium for MTs Al-Ittihad teachers was based on the problem identified by the Postgraduate School Faculty service team, Universitas Lancang Kuning, namely the lack of knowledge about digital literacy in contemporary learning. For this reason, training in using technology applications in learning should be provided. This workshop was held in May 2023 at MTs Al-Ittihad School with 20 participants for 4 hours. To measure the level of teacher understanding, the service team provided questionnaires in the sessions before and after activities. The results of the pre-test regarding the use of technology applications namely ChatGPT, Vocaroo, and Tricider, showed that 93% -100% of the participants did not know about these technology applications. However, after the training was given, the results of the post test showed that 100% of the participants understood and could use the learning technology applications provided. Finally, the service team concluded that teachers really need knowledge about ICT empowerment in order to improve the achievement of learning outcomes. Workshop penggunaan aplikasi teknologi sebagai media pembelajaran bagi guru MTs Al-Ittihad ini dilaksanakan berdasarkan masalah yang diidentifikasi oleh tim pengabdian Fakultas Sekolah Pascasarjana Universitas Lancang Kuning yaitu kurangnya pengetahuan tentang literasi digital dalam pembelajaran kekinian. Untuk itu, pelatihan menggunakan aplikasi teknologi dalam pembelajaran diberikan. Kegiatan workshop ini dilaksanakan pada bulan Mei 2023 di Sekolah MTs Al- Ittihad dengan 20 peserta selama 4 jam. Untuk mengukur tingkat pemahaman guru pada kegiatan pelatihan ini, tim pelaksana pengabdian memberikan angket pada sesi sebelum dan sesudah kegiatan workshop. Hasil angket pre-test dari penggunaan aplikasi teknologi sebagai media pembelajaran yaitu ChatGPT, Vocaroo, dan Tricider yang diberikan menunjukkan 93%-100% dari peserta belum mengetahui aplikasi teknologi tersebut. Namun, setelah pelatihan diberikan, hasil angket post test menunjukkan 100% peserta memahami dan dapat menggunakan aplikasi teknologi pembelajaran yang diberikan. Akhirnya, tim pengabdian menyimpulkan bahwa guru-guru memang memerlukan pengetahuan tentang pemberdayaan TIK dalam rangka meningkatkan pencapaian hasil belajar.